Community readiness for the program of all-inclusive care for the elderly (PACE): A qualitative study with Korean Americans in Los Angeles - Juyoung Park; Seo-Yun Choi; Nan Sook Park; Jong Won Min; Tei Park; Yuri Jang (PLoS ONE, 2026)
The Program of All-Inclusive Care for the Elderly (PACE), which provides integrated medical, social, and personal healthcare to help older adults remain in their homes and communities, has been a successful long-term care services and support (LTSS) model. Yet little is known about how racial and ethnic minority communities perceive and respond to this program. Guided by the Community Readiness Model (CRM), this explorative qualitative study examined readiness for PACE in Korean American communities in Los Angeles. Data were collected from 28 participants, including two focus groups with 19 older adults (age ≥ 55) and nine individual interviews with family caregivers and health and social service providers. Four major themes emerged: (1) Awareness, (2) Perceived Benefits, (3) Perceived Barriers and Concerns, and (4) Recommendations for Implementation and Outreach. In general, awareness of PACE was low among participants, and many had unclear or incorrect understanding of the program. Perceived benefits included the ability to age in place, access to coordinated care at a single setting, opportunities for social engagement, and reduced caregiving burden. Concerns noted by participants included the need to switch physicians, possible disruption of existing services such as In-Home Supportive Services, and uncertainty about the qualifications of PACE providers. Recommendations highlighted the importance of culturally tailored outreach, a more descriptive program name, strong leadership, a cooperative interdisciplinary team culture, and staffing that combines clinical expertise with compassion and cultural sensitivity. These findings suggest that introducing PACE in the Korean American community requires intentional adaptation to address both cultural expectations and structural barriers. This study offers insights into how the PACE model can be more effectively introduced, adapted, and sustained in racial and ethnic minority communities that have not been fully engaged by LTSS outreach and delivery efforts.